2022
DOI: 10.3390/su142114210
|View full text |Cite
|
Sign up to set email alerts
|

Promising Technology Analysis and Patent Roadmap Development in the Hydrogen Supply Chain

Abstract: Hydrogen energy, one of the energy sources of the future, represents a substantial issue which affects the industries and national technologies that will develop in the future. In order to utilize hydrogen energy, a hydrogen supply chain is required so that hydrogen can be processed and transported to vehicles. It is helpful for technology and policy development to analyze technologies necessary to charge the hydrogen energy generated into vehicles through the supply chain to discover technologies with high po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Establishing a hydrogen supply chain is fundamental for achieving a hydrogen economy [17]. A hydrogen supply chain should encompass hydrogen production, hydrogen storage, hydrogen transportation and delivery, and hydrogen utilization [18,19]. The key components of a hydrogen supply chain are illustrated in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…Establishing a hydrogen supply chain is fundamental for achieving a hydrogen economy [17]. A hydrogen supply chain should encompass hydrogen production, hydrogen storage, hydrogen transportation and delivery, and hydrogen utilization [18,19]. The key components of a hydrogen supply chain are illustrated in Figure 2.…”
Section: Introductionmentioning
confidence: 99%
“…With the emphasis of the global society on environmental protection and sustainable development, an increasing number of scholars have become devoted to research on hydrogen patents. Yu et al [1] proposed that promising technologies that will be the core of the hydrogen fuel supply chain in the future were identified using the published patents and research paper database (DB) in Korea, the United States, Europe, China, and Japan. Baumann et al [2] found that the patenting activity of Germany is considered lower in comparison to countries such as Japan, China, and the US.…”
Section: Introductionmentioning
confidence: 99%